Searching for entrepreneurship : The perception of the phenomenon - Andrzejczyk, Angelika (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
In the article, the picture of entrepreneurship, its empirical/conceptual context, discipline diversity and orientation emerging from the bibliography searching process according to relevance in Google Scholar were assessed. Preliminarily, a comparison with other forms of obtaining scientific information about entrepreneurship was made. Some evidence has been found on the directions of the possible influence of this source of knowledge on the perception of the entrepreneurship phenomenon. The popular scientific databases/search engines in terms of entrepreneurship terms retrieval were compared. After selecting Google Scholar, a set of articles about entrepreneurship was analysed. The method of literature analysis and criticism was used. In order to develop interest in entrepreneurship, it is necessary to analyse the publicly available sources of economic knowledge more often in order to prevent possible distortions of the image of phenomena and efficient detection of unfair practices.The research popularity of entrepreneurship is high, but the limitations faced by readers interested in it may slow down the progress of scientists’ achievements and the creation of a separate field, and may even cause a loop/stagnation disproportionate to the interest in this area of science. It is worth paying attention to the popularization of scientific databases/search engines, and becoming familiarized with the results of the research in this field.
Keywords: entrepreneurship; entrepreneur; economic bibliographies; sources of knowledge; ethics